The new Basle capital accord and developing countries: Issues, implications and policy proposals - Stephany Griffith-Jones; Stephen Spratt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper argues that, if implemented in its current form, the new Basle Capital Accord will adversely effect developing sovereigns, corporates and banks wishing to borrow in international markets. This impact will result from the major banks' lending patterns being altered by the adoption of internal ratings based approaches, leading to a significant reduction of bank, and/or a sharp increase in the cost of international borrowing for many developing countries. Greater use of banks' internal risk management systems is also inherently pro-cyclical and therefore likely to amplify the economic cycle, thus increasing both the frequency and scale of crises.
Keywords: F34; G18; G21; 330; risk-management; internal-ratings; pro-cyclicality; net impact; Eigenkapitalvorschriften; Entwicklungsländer; Basel II